Designing an inclusive chemistry learning environment for intellectual disabilities through Universal Design for Learning (UDL) in periodic properties elements - Virani, Hana Salsabila; Santoso, Teguh Bedjo; Sari, Rahmania Fitrah; Asih, Findiyani Ernawati; Novita, Dian (Education and Development Research, 2026)
Inclusive education is a learning approach that accommodate the diverse abilities of students, including students with intellectual disabilities. However, implementation in chemistry learning which has abstract concepts, presents challenges for students with intellectual disabilities. Conventional chemistry learning tends to be limited to fulfilling cognitive needs. This research aims to examine the implementation Universal Design for Learning (UDL) principles in building an inclusive learning environment and support conceptual understanding of periodic properties This research employed a mixed-method embedded design, with qualitative data serving as the primary data and quantitative data supporting it. The subjects were three eleventh-grade students with intellectual disabilities at Senior High School 10 Surabaya. Qualitative data were gathered by means of observation, interviews, and video documentation, that processed using NVivo 11 software, quantitative data were obtained through pretests and posttests, analyzed use N-gain values. The results from this research demonstrate that implementation of UDL through the principles of representation, engagement, and action and expression was able to build an inclusive learning environment by providing flexible learning access and tailored to students' needs. In addition, the results of N-gain analysis reveal an improvement in conceptual understanding with a high category (average N-gain = 0.93). These findings confirm highlight that the application of UDL as an approach to more inclusive in chemistry learning environments for students with intellectual disabilities.